Pengaruh Gaya Kepemimpinan Dan Stres Kerja Terhadap Kinerja Pegawai Pada Dinas Kependudukan Dan Catatan Sipil Kota Makassar - Nurannisa Nurannisa; Syarifuddin Sulaiman; Zalkha Soraya (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the influence of leadership style and work stress on employee performance at the Population and Civil Registration Office of Makassar City. This is a quantitative research study. The sample consists of all 54 employees at the Population and Civil Registration Office, selected using a saturated sampling technique. The type of data used is quantitative data obtained from questionnaires distributed based on the research problem. Data collection techniques include observation, documentation, and questionnaire distribution.. Based on statistical analysis using SPSS version 26, the results showed that leadership style has a positive and significant effect on employee performance, with a t-count value of 2.515 > 2,008 and a significance value of 0.015 < 0.05. Work stress also has a positive and significant effect on employee performance, with a t-count value of 2.422 > 2,008 and a significance value of 0.019 < 0.05. Therefore, leadership style and work stress should be continuously improved and effectively managed, as both have a significant impact on enhancing employee performance.